Kajian Mineral Lempung pada Kejadian Bencana Longsorlahan di Pegunungan Kulonprogo Daerah Istimewa Yogyakarta - Kuswaji Dwi Priyono (Forum Geografi, 2012)
The aims of this study is know the characteristic of the clay mineral types in the landslides occurrence sites, and to examine the relation between the clay and intensity of landslides in Kulonprogo Mountains. Understanding of clay type character will be very important in the landslides disaster mitigation in the area landslides disturbed. This study use survey method, purposive sampling and qualitative analysis. At each landslides location soil sample was taken to determine the clay characteristic. The clay types was analysed by by X-Ray Diffraction. Spatial distribution of landslides based on the landforms unit supported by topographical map, geological map, and Digital Elevation Modell (DEM). The result of this study shows that clay mineral average in this landslides study location: caolin (70,64%), smectit/montmorillonit (15,12%), halite (4,33%), illite (2,99%), quartz (2,91%), cristabolite (2,28%), feldspar (1,34%), and goethite (0,39%). Clay mineral composition show that the interaction over land forming factors which make caolin forming in great quantities possible.